Psychological problems among elementary and high school educators in Canada: association with sick days in the prior school year - Agyapong, Belinda; Wei, Yifeng; da Luz Dias, Raquel; Orimalade, Ade; Brett-MacLean, Pamela; Agyapong, Vincent Israel Opoku (Frontiers in Psychology, 2024)
Increased sick leave among educators can detrimentally impact students' productivity, and academic achievement. It remains unknown whether the number of sick days taken by educators in the preceding school year correlates with the prevalence or severity of psychological problems among educators in the subsequent school year.This study aimed to examine the number of self-reported sick days taken by educators in three Canadian provinces during the 2021/2022 academic year and its association with measures of stress, burnout, low resilience, depression, and anxiety during the 2022/2023 school year.